2016
DOI: 10.1044/2016_ajslp-15-0145
|View full text |Cite
|
Sign up to set email alerts
|

Looking for a Location: Dissociated Effects of Event-Related Plausibility and Verb–Argument Information on Predictive Processing in Aphasia

Abstract: a Purpose: This study examined the influence of verbargument information and event-related plausibility on prediction of upcoming event locations in people with aphasia, as well as older and younger, neurotypical adults. It investigated how these types of information interact during anticipatory processing and how the ability to take advantage of the different types of information is affected by aphasia. Method: This study used a modified visual-world task to examine eye movements and offline photo selection. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 85 publications
1
12
0
Order By: Relevance
“…This prediction is not unique to rational adaptation, nor is it surprising given that aphasia, by definition, impairs language. For example, although linguistic and conceptual knowledge were also independent in the study by Hayes et al (2016) , they only found evidence that people with aphasia relied less on linguistic knowledge than neurotypical controls did. The current study goes beyond this in showing an increase in the use of conceptual knowledge for people with aphasia.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…This prediction is not unique to rational adaptation, nor is it surprising given that aphasia, by definition, impairs language. For example, although linguistic and conceptual knowledge were also independent in the study by Hayes et al (2016) , they only found evidence that people with aphasia relied less on linguistic knowledge than neurotypical controls did. The current study goes beyond this in showing an increase in the use of conceptual knowledge for people with aphasia.…”
Section: Discussionmentioning
confidence: 80%
“…Another critical contribution of this study is that it separately examines automatic facilitatory effects of linguistic and conceptual information types, which are independent of one another in this study design. Much of the previous evidence that is consistent with rational adaption in aphasia could be explained by the fact that people with aphasia show less reliance on linguistic knowledge than neurotypicals (e.g., Hayes et al, 2016 ; Warren et al, 2017 ). This prediction is not unique to rational adaptation, nor is it surprising given that aphasia, by definition, impairs language.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…But in direct contrast, in an experiment testing predictive language processing, Milburn et al (2016) found that the proportion and timing of predictive looks to a target object were guided by world knowledge and unaffected by the presence of potentially predictive selectional restrictions. In another visual world experiment, Hayes et al (2016) similarly found that world knowledge about event likelihood was used as quickly, if not more quickly, than verb-based expectations for the existence of an upcoming locative argument. Venhuizen et al's (2019) model in its current form seems unlikely to be able to capture these task-based differences, given that it only models processing difficulty during reading, it is not clear whether it represents verb-based knowledge like selectional restrictions and expectations for upcoming arguments, and it has no mechanism for capturing fine-grained differences in when different kinds of knowledge are used.…”
Section: Tradeoffs Between Reliance On Linguistic and World Knowledge In Language Processingmentioning
confidence: 90%
“…The VWP has been used to study, among others, phonological effects on word recognition (Allopenna et al 1998), facilitative effects of selectional restrictions (Altmann and Kamide 1999), the mental representation of scenes (Altmann and Kamide 2009), and the role of event knowledge in predictive processing (Milburn et al 2016). Furthermore, the VWP is easy for participants to complete: participants are often required only to ''look and listen'' or to follow simple instructions, making it ideal for use in populations, such as older adults (Hayes et al 2016), people with aphasia (Mack et al 2013), young children (Borovsky et al 2012) or deficit populations (Norbury 2017;Vulchanova et al 2019).…”
Section: Language Comprehension and Visual Context: An Integrated Permentioning
confidence: 99%